PENGARUH ROA DAN EPS TERHADAP HARGA SAHAM DENGAN INFLASI SEBAGAI VARIABEL MODERASI (Studi Kasus Pada Perusahaan Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2019-2023): menelaah ebih jauh bagaimana ROA dan EPS dapat berpengaruh terhadap harga saham dan dengan inflasi sebagai faktor eksternal apakah bisa mempengaruhi interaksi antar variabel internal - Inest Ruth Marsaulina Siregar; Elga Yulindisti; Muhsin Muhsin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze how Return on Assets (ROA) and Earning Per Share (EPS) influence stock prices, with inflation acting as a moderating variable, focusing on food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The study employs a quantitative method and utilizes Moderated Regression Analysis (MRA) to examine both direct and interaction effects. The results reveal that ROA has a significant negative effect on stock prices, while EPS has a significant positive effect. These findings indicate that an increase in ROA does not necessarily lead to higher stock prices, potentially due to high efficiency and negative investor perceptions of rising earnings, especially post-pandemic and during inflationary periods. EPS proves to be a more reliable indicator for predicting stock prices in this sector. Collectively, ROA, EPS, and inflation explain 69.4% of the variation in stock prices. This research highlights the importance of companies maintaining EPS to boost market confidence and advises investors to consider earnings quality and external dynamics when making investment decisions.